Poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) copolymer beads as support for covalent immobilization of L-aminoacylase - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Nene, Sanjay N. (Reactive & Functional Polymers, 2012)
Porous epoxy-activated copolymer beads were synthesized as support for the covalent immobilization of Aspergillus melleus L-aminoacylase. Here, a series of copolymer bead were synthesized using either glycidyl methacrylate (GMA) or ally] glycidyl ether (AGE) as monomer units and ethylene glycol dimethacrylate (EGDM) as cross-linking agent. The effect of monomer used and the effect of amount of cross-linking agent on covalent immobilization of aminoacylase were studied. Furthermore, the effect of porogen on immobilization of aminoacylase was also evaluated. AGE-co-EGDM copolymer beads gave higher binding of aminoacylase than GMA-co-EGDM copolymer beads. AGE-co-EGDM copolymer beads synthesized with lauryl alcohol as porogen and having 150% cross-linked density (i.e. AGE-(L)-150) gave maximum enzyme binding. Under optimum conditions, AGE-(L)-150 copolymer beads gave about 130 U/g of aminoacylase activity which corresponds to 72.24% of activity yield. Immobilized aminoacylase showed a broader pH, higher temperature and extended storage stability. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization; Epoxy-activated support; L-Aminoacylase

Preparation of cross-linked enzyme aggregates of L-aminoacylase via co-aggregation with polyethyleneimine - Vaidya, Bhalchandra K.; Kuwar, Suyog S.; Golegaonkar, Sandeep B.; Nene, Sanjay N. (Journal of Molecular Catalysis B-Enzymatic, 2012)
L-Aminoacylase from Aspergillus melleus was co-aggregated with polyethyleneimine and subsequently cross-linked with glutaraldehyde to obtain aminoacylase-polyethyleneimine cross-linked enzyme aggregates (termed as AP-CLEA). Under the optimum conditions, AP-CLEA expressed 74.9% activity recovery and 81.2% aggregation yield. The said method of co-aggregation and cross-linking significantly improved the catalytic stability of L-aminoacylase with respect to temperature and storage. AP-CLEA were employed for enantioselective synthesis of three unnatural amino acids (namely: phenylglycine, homophenylalanine and 2-naphthylalanine) via chiral resolution of their ester-. amide- and N-acetyl derivatives. The enantioselectivity of AP-CLEA was the highest for hydrolysis of amino acid amides; was moderate for hydrolysis of N-acetyl amino acids and was the least for hydrolysis of amino acid esters. Furthermore, AP-CLEA were found to retain more than 92% of the initial activity after five consecutive batches of (RS)-homophenylalanine hydrolysis suggesting an adequate operational stability of the biocatalyst. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: chiral resolution; Cross-linked enzyme aggregates; L-Aminoacylase; Polyethyleneimine; Unnatural amino acids